THE EFFECTIVENESS OF PROJECT-BASED LEARNING MODEL WITH STEM APPROACH IN ENHANCING STUDENTS' CREATIVE THINKING SKILLS - Nurain Ain Djafar; Jusna Ahmad; Masra Latjompoh (Universitas Negeri Medan, 2023)
The crux of this study involves the formulation of a project-based learning model using the STEM approach, aimed at delineating the efficacy parameters for augmenting students' creative thinking proficiencies within the context of SMK Negeri Model Gorontalo. Employing a Research and Development framework, the study encompasses successive phases of inquiry, including preliminary investigation, blueprinting, compositional arrangement of the preliminary prototype, validation of the prototype, experimental implementation, and finalization of the product. The findings reveal that the efficacy facet of the project-based model coupled with the STEM approach falls within the range of 0.3 < g < 0.7, thereby situating it within the intermediate classification. This inference is substantiated by the discerned n-gain percentage scores denoting the progression in creative thinking capabilities. Furthermore, outcomes stemming from student questionnaires administered during the limited scope field trials exhibit a response rate of 87%, whereas the broader public field testing elicits an 85.8% response rate. These affirmative percentages, as gleaned from student feedback, corroborate the efficaciousness of the project-based instructional model fortified by the STEM approach in fostering the augmentation of students' creative thinking proficiencies.